Development of a Web-Based Campus Facility Complaint Information System Prototype Using Rapid Application Development - Muh. Akhyarul Insan; Fajar Octanouva; Nur Vitriati; Sabila Wahyu Pratama; Aditya Sendy Ardiansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Campus facility complaint management requires a structured mechanism for recording, monitoring, and tracing reported problems to support transparent service processes. This study developed a web-based Campus Facility Complaint Information System (SIPFAS) prototype using the Rapid Application Development (RAD) method. The development process comprised requirement planning, user design, construction, and cutover and verification stages, with the prototype designed to support service information access, authentication, complaint submission, status monitoring, and complaint-detail retrieval. Evaluation focused on the public page, login interface, user dashboard, and complaint-detail page containing the status history of complaint PGD-002. Interface consistency verification showed that the dashboard summary was arithmetically consistent, with 3 complaints in Waiting status, 4 in In Process status, and 5 in Completed status, resulting in a total of 12 complaints. The PGD-002 identity was also traceable across the dashboard and complaint-detail interfaces. However, two inconsistencies were identified, namely a discrepancy between the complaint date of 19 August 2026 and the timeline submission timestamp of 20 August 2026 at 09:14, and a mismatch between the administrator-verification timestamp and its visual state. The prototype establishes a structured complaint-monitoring workflow, although data consistency, functional testing, authorization, backend persistence, and usability evaluation require further verification before full implementation.